Does age affect job and organisational engagement and employee performance in Zimbabwe’s health sector? - Nyengeterai Makumbe; Nhamo Mashavira; Munyaradzi Chikove; Frank R. Matenda; Mabutho Sibanda (SA Journal of Human Resource Management)
Orientation: The ageing healthcare workforce has been an issue of concern in the health sector over the recent years. This unique demographic challenge poses numerous challenges like knowledge loss and possible skill shortages.